Examining the efficacy of dance movement and music mixed treatment on social communication impairment in children with autism — Based on family parent-child situation - Ren, Huiting; Ren, Guanghao; Zhan, Yuqi; Jia, Zhichun (Frontiers in Psychology, 2022)
Children with ASD have obvious social communication impairments, but the existing studies only focus on the effect of MT or DMT therapy alone, and there are few studies on the intervention of social communication impairments in children with ASD in the parent-child family situation. This study designed a mixed intervention program of MT and DMT to conduct 3-month intervention and training for ASD children based on parent-child family situations. Based on the experimental design of pre-test and post-test in the experimental group and the control group, the two scales, CARS and ATEC, were used to evaluate the symptoms of ASD and the evaluation of the intervention effect. The experimental results showed that there was no significant difference in the CARS pre-test scores between the experimental group and the control group(t=1.218,p>0.05). There was no significant difference in ATEC pretest scores (t=0.546, p>0.05. F=0.074, p>0.05, partial Eta square =0.003). There was no significant difference in the pre- and post-test scores of CARS in the control group (t=0.635, p>0.05), and there was no significant difference in the pre- and post-test scores of ATEC in the control group (t=0.027, p>0.05. F=5.251, p>0.05, partial Eta square=0.313 ). There was a significant difference in the pre- and post-test scores of CARS in the experimental group (t=4.327, p<0.05), and a significant difference in the pre- and post-test scores of ATEC in the experimental group (t=5.763, p<0.01. F=32.615, p<0.01, partial Eta square=0.759), The post-test scores were lower than the pre-test scores. It shows that the mixed intervention of MT and DMT in the parent-child family situation alleviates the autism of ASD children and improves the social barriers of ASD children.